Serpent's promise : the Bible retold as science - Jones, Steve, 1944- (London : Abacus, 2014)
Revisits Bible stories as seen through the lens of modern science, attempting to determine if humans are really descended from Adam and Eve and if Noah's great flood was actually a representation of the end of the Ice Age.
Includes index.
Keywords: Bible and science; Religion and science; Nature in the Bible